Sensitivity Enhancement Of Optical Fiber Sensor For Liquid Sensing Applications By Using Mach-Zehnder Interferometer - Sulaiman, Nur Hidayah (2018)
Liquid sensing application plays an important role in biological,chemical and food industries.A conventional electrical based sensor is exposed to electromagnetic interference (EMI) which generates the electrical sparks. Hence,the fiber optic sensor (FOS) has attracted a great interest in sensing applications due to the immunity to EMI,high sensitivity and compact size.Interferometer is commonly used in the development of the FOS in liquid measuring system.In this research project,the FOS has been employed for liquid sensing application by using a Mach–Zehnder Interferometer (MZI).There are two main MZI structures that involved in this research,which are Singlemode-Multimode-Singlemode (SMS) and Multimode-Singlemode-Multimode (MSM) structure that provides low cost of fabrication.The device was developed by using simple and less complex fabrication which is fusion arc splicing technique for splicing the three main sections of FOS.The sensitivity analysis was tested on different liquid concentration such as water,1.0 mol sucrose and oil with the refractive index of 1.333 RIU,1.384 RIU and 1.464 RIU respectively.This research manipulated the sensing-region section to analyze the response of FOS towards different liquid concentration.Firstly,the length of the sensing region was varied to 4 cm,8 cm and 12 cm prior to sensitivity enhancement method.The resultant of resonance wavelength shifting generates different sensitivity and the length of the sensor area which demonstrated the highest sensitivity was selected for the next sensitivity enhancement process.The sensitivity enhancement process for this research is based on the chemical etching and macrobending effect that aimed to generate more evanescence field at the sensing region. According to the etching process analysis,time taken for each sensing-region to reach 55 μm diameter was 16 minutes for SMS structure and 23 minutes for MSM structure.Meanwhile for the macrobending effect,the sensing-region with a bending diameter of 2.8 cm,3.3 cm and 4.0 cm were analyzed.The results of the FOS with and without the sensitivity enhancement were observed.This research demonstrated improvement sensitivity by 1663.31% for SMS structure and 827.08% for MSM structure.